If the roots of the equation (b-c)x^2+(c-a)x+(a-b)=0 are equal then show that a,b,c are in A.P.

Asked by aashiya kanha sharma | 2nd Oct, 2013, 12:21: AM

Expert Answer:

(b-c)x^2+(c-a)x+(a-b)=0
here x=1 will be one of the root because sum of coff. is zero.
now as both roots are  equal so x=1 will be repeated root.
now product of roots=1*1=(a-b)/(b-c)
a-b=b-c
2b=a+c
a,b,c are in a.p.

Answered by  | 2nd Oct, 2013, 12:41: AM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.